Composizione e improvvisazione: dove sta la differenza? - Daniele Goldoni (Aisthesis, 2014)
Improvisation is often conceived as making music without reading a score. This interpretation derives from the Western identification of composition with written music. But “improvisation” too is a form of composition – and not just in “real time” – with aims and criteria that differ from those of written music. Today the interest in improvisation is growing –and even changing with respect to the postwar years – in connection with changes in music, sound and social relationships, reflecting new media developments.